2019
DOI: 10.31219/osf.io/h2mva
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of spelling treatment approaches for learners with dyslexia – A meta-analysis and systematic review

Abstract: This systematic review and meta-analysis investigated the efficacy of spelling interventions for the remediation of dyslexia and spelling deficits. Theoretically important moderators, such as the treatment approach as well as orthographic and sample characteristics, were also considered. Thirty-four controlled trials that evaluated spelling interventions in children, adolescents and adults with dyslexia and spelling deficits were included. Results show that treatment approaches using phonics, orthographic (gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 104 publications
1
5
0
Order By: Relevance
“…Considering the relatively short duration of the intervention (only eight lessons), it can be concluded that this evidence provides a positive outlook for incorporating MSL methodology while teaching dyslexic students. Other studies that have investigated the use and effects of MSL and phonological interventions in spelling skills strongly indicate that dyslexic learners can increase their spelling abilities (Galuschka et al, 2020;Lim & Oei, 2015;Nijakowska, 2010;Snowling et al, 2020). The findings are also in agreement with the consensus that dyslexic learners require specific interventions to compensate for their deficits (Kormos, 2017, p. 118).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 78%
See 2 more Smart Citations
“…Considering the relatively short duration of the intervention (only eight lessons), it can be concluded that this evidence provides a positive outlook for incorporating MSL methodology while teaching dyslexic students. Other studies that have investigated the use and effects of MSL and phonological interventions in spelling skills strongly indicate that dyslexic learners can increase their spelling abilities (Galuschka et al, 2020;Lim & Oei, 2015;Nijakowska, 2010;Snowling et al, 2020). The findings are also in agreement with the consensus that dyslexic learners require specific interventions to compensate for their deficits (Kormos, 2017, p. 118).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 78%
“…In general, dyslexic students require specific interventions to develop their literacy (Nijakowska, 2010). While reviewing and analysing an extensive list of previously conducted intervention studies, Galuschka et al (2020) found that children who took part in spelling interventions improved their spelling skills substantially compared to children who attended regular lessons. The relationship between phoneme and grapheme should be made explicit in any intervention (Montgomery, 2006), while special emphasis should be placed on spelling, which seems to be a persistent difficulty for dyslexic learners, including those in Norway (Helland & Kaasa, 2005).…”
Section: Dyslexia and English Language Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Space precludes a comprehensive review of reading interventions, however, as might be expected from the theoretical framework presented here, children with dyslexia benefit from teaching that directly targets word‐level decoding as well as underlying skills (spelling‐sound relationships and phonological skills, see Galuschka et al, 2019; McArthur et al, 2018 for reviews). There is also some evidence that, for children with dyslexia, interventions to improve their decoding problems lead to improvements in reading comprehension (since for these children the principal limiting factor for comprehension is their low level of reading accuracy).…”
Section: Educational Implicationsmentioning
confidence: 99%
“…These findings provide the theoretical motivation for early reading intervention programs ( Hatcher et al, 2006 ; Suggate, 2016 ). The most successful reading intervention programs combine phonological awareness training with structured reading explicit instruction (e.g., Hatcher et al, 1994 ; Lovett et al, 2003 ; Hatcher et al, 2006 ; Snowling and Hulme, 2011 ; Galuschka et al, 2019 ) using self-correction strategies ( Williams et al, 2016 ). A meta-analysis assessment of the long-term effects of phonemic awareness shows that the impact of phonemic awareness interventions was maintained along the time and transferred to non-targeted skills such as letter-sound knowledge with consequences on reading comprehension ( Suggate, 2016 ).…”
Section: Introductionmentioning
confidence: 99%